(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the chemical synthesis methods of drug substances and the relationship between their chemical structure and pharmacological activity. Chemical synthesis plays a key role in the development of new pharmaceuticals, with small changes in molecular structure significantly impacting drug efficacy and safety. The article provides detailed information on the synthesis of natural and synthetic drugs, structural modifications, their biological effects, and modern synthesis technologies.